Determinants of long acting and permanent contraceptive methods utilization among married women of reproductive age groups in western Ethiopia: a cross-sectional study - Melka, Alemu Sufa (Pan Afr Med J, 2015)
INTRODUCTION: In Ethiopia information on the level of utilization of the long term and permanent contraceptive methods and associated factorsis lacking. The aim of this study was to understand the determinant factors of long acting and permanent contraceptive methods use among married women of reproductive age in Western Ethiopia. METHODS: A community based cross- sectional study design was employed. Multi stage sampling was used to select 1003 study participants. Data was collected from April 10 to April 25,2014 using a pre- tested structured questionnaire. The data were entered using Epi-info version 3.5.1 and exported to SPSS version 20 for analysis. Multivariate logistic regression analysis was done to identify predictors of long acting and permanent contraceptive methods at 95% CL. RESULTS: Use of long acting and permanent contraceptive methods in this study was found to be 20%. Survey results showed a significant positive association between utilization of long acting and permanent contraceptive methods and women's education (AOR = 1.72, 95%CI = 1.02 - 3.05), women's occupation (AOR = 2.01, 95% CI = 1.11 -3.58), number of live children (AOR = 2.42, 95% CI: 1.46- 4.02), joint fertility related decision (AOR = 6.11, 95% CI: 2.29- 16.30), having radio/TV (AOR = 2.31, 95% CI: 1.40 - 3.80), and discussion with health care provider about long acting and permanent contraceptive methods (AOR = 13.72, 95% CI: 8.37 - 22.47). CONCLUSION: Efforts need to be aimed at women empowerment, health education, and encouraging open discussion of family planning by couples